A dynamic and tribological simulation of a monolayer graphene sheet for a carbon atom‐graphene contact. (12th December 2018) - Palaiologos, Alexandros; Grigoriadis, Kyriakos; Zavos, Anastasios; Nikolakopoulos, Pantelis G.
Abstract: This study focuses on the dynamic and tribological characterisation of a single‐layer graphene sheet (SLGS). A 10 × 10 nm graphene model is developed, which is modally analysed for both zigzag and armchair lattices, thus enabling the examination of chirality effect on the SLGS' eigenfrequencies. The tribological analysis consists of the same SLGS model and a carbon atom simulating the graphene tip. The carbon atom is set to move on multiple paths to examine the importance of the path's position over the sheet. The friction forces applied on the tip during its movement can be calculated. The carbon atom tip is interlinked with the graphene atoms via the Lennard‐Jones model, characterising the real contact area. Spring elements mimic the interatomic forces, while beam and mass elements simulate the graphene's C─C covalent bonds and atoms, respectively, on a finite element simulation verified by the Prandtl‐Tomlinson model. It is perceived a strong stick‐slip effect on the friction force's areal pattern, which can be verified by the Prandtl‐Tomlinson theory of the atomic scale friction. It also became clear the effect of chirality, on graphene's tribological behaviour, after the differences in the calculated friction forces. Finally, an increase in the coefficient of friction analogous to the increase of the vertical load, due to graphene's deformation, is determined, while in the zigzag lattice, the coefficient of friction appears to be significantly lower that the armchair one.